Alcune poetesse italiane del cinquecento (Italian female poets of the 16th century) - Cattaneo, Graziella (My University, 2014)
The present M.A thesis reviews and analyzes a previously underestimated area of sixteenth century Italian literature, namely the stylized lyric poetry of five representative female authors, whose production spans the whole period. The differences between the various poetesses, even inside their conventional thematic choices, are considerable. They allow us to identify a variety of expressional modes in the development of a fairly limited stylistic canon whose intuitive rules were felt by each of the writers. These differences are seen to be determined both by the individual personality of each poetess and by the single perspective according to which each chose to interpret the role of the lyric poet. Hence we can observe, in broad lines, the intellectualized lyric of Vittoria Colonna, the passionate manner of Gaspara Stampa, the more rational poetics of Veronica Gambara, all in more or less direct contrast with the freer manner of Veronica Franco and the tormented self-dramatization of Isabella Morra, The study argues that this diversity of treatment accounts for the comparativist interest which criticism should take in coming to terms with both the biographical background and poetic results of five significant female writers- Thus their work is compared both from a historical viewpoint and from specific personal angles which attempt to highlight their occasional openings towards a strikingly modern formulation of the emotion in writing.
A dissertation submitted to the Faculty of Arts University of the Witwatersrand, Johannesburg for the Degree of Master of Arts Johannesburg, 1983